A Review on The Benefits of Probiotics as Fermented Food against Several Diseases - Nasri, Nasri; Silalahi, Jansen; Kaban, Vera Estefania; Satria, Denny (Journal Akademik Universitas Swiss German, 2023)
Fermentation is a natural process when microorganisms such as yeast and bacteria convert carbohydrates such as starch and sugar into alcohol or acid. Some fermented products from microorganisms can be processed into foods that can be consumed and provide good health effects for the body. Fermented foods such as kefir, tempeh, natto, and kimchi are foods that produce probiotic bacteria, which are good bacteria that have a beneficial effect on the host when consumed in sufficient quantities (about 108–1011 CFU/mL). If probiotics are consumed in combination with prebiotics, they will have a synergistic effect called "synbiotics" and will increase the benefits of probiotics. Several in vitro, in vivo, and clinical studies have shown that probiotics can help with diseases like diarrhea, high cholesterol, diabetes, colon cancer, and dyslipidemia